Jaulung Wismar Saragih: A Simalungun Contextual Theology - Sipayung, Parulihan (International journal of Asian christianity, 2023)
This study explores the theological significance of Jaulung Wismar Saragih (1888-1968), the first-generation Christian, ordained pastor and theologian from the Simalungun ethnic group. He was also the first local person to translate the Bible into his local language in the Indonesian context. Saragih’s theological thinking foregrounded Indonesian postcolonial contextual theology regarding the identity and role of the church for social transformation in the context of religious pluralism and the struggle for gender justice, human freedom, and dignity. This study is an appreciative inquiry from a postcolonial theo-historical and biographical reconstruction of Saragih’s contextual theology and its public theological implications for contemporary Indonesia.